Design and Development of an Automatic Clothes Drying System Based on Microcontroller - Rosmiati Jamiah; Riswandi (Universitas Islam Kuantan Singingi, 2026)
The conventional clothes drying process is highly dependent on weather conditions and requires continuous human supervision, which reduces efficiency. This study aims to design and implement an automatic clothes drying system based on a microcontroller that operates independently according to environmental conditions. The system uses a microcontroller as the main controller integrated with temperature and humidity sensors to detect air conditions and a light sensor to identify sunlight intensity. DC motors and relays are employed as actuators to control the drying mechanism. The research method includes hardware design, software development, system implementation, and performance testing. The results show that the system can automatically determine the drying process based on sensor inputs and respond effectively to environmental changes. This system is expected to improve efficiency and provide a practical solution for automatic household clothes drying.